2000
DOI: 10.1074/jbc.m002713200
|View full text |Cite
|
Sign up to set email alerts
|

Human Cdc7-related Kinase Complex

Abstract: huCdc7 encodes a catalytic subunit for Saccharomyces cerevisae Cdc7-related kinase complex of human. ASK, whose expression is cell cycle-regulated, binds and activates huCdc7 kinase in a cell cycle-dependent manner (Kumagai, H., Sato, N., Yamada, M., Mahony, D., Seghezzi, W., Lees, E., Arai, K., and Masai, H. (1999) Mol. Cell. Biol. 19, 5083-5095). We have expressed huCdc7 complexed with ASK regulatory subunit using the insect cell expression system. To facilitate purification of the kinase complex, glutathion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 48 publications
4
76
1
Order By: Relevance
“…Annotation of the human Mcm2 amino acid sequence has been recently updated in its N terminus, and here we refer to its new Swiss Prot accession number, P49736. We and others have previously shown that an Mcm2 N-terminal fragment, corresponding to amino acids 10 -294, is a good substrate for both Cdc7 and CDKs (9,18,20). We extended these observations and also found that CK2 kinase, which has been proposed to modulate DNA replication by phosphorylating multiple substrates (17), efficiently uses the Mcm2 N-terminal fragment as a substrate.…”
Section: Identification Of Mcm2supporting
confidence: 66%
See 2 more Smart Citations
“…Annotation of the human Mcm2 amino acid sequence has been recently updated in its N terminus, and here we refer to its new Swiss Prot accession number, P49736. We and others have previously shown that an Mcm2 N-terminal fragment, corresponding to amino acids 10 -294, is a good substrate for both Cdc7 and CDKs (9,18,20). We extended these observations and also found that CK2 kinase, which has been proposed to modulate DNA replication by phosphorylating multiple substrates (17), efficiently uses the Mcm2 N-terminal fragment as a substrate.…”
Section: Identification Of Mcm2supporting
confidence: 66%
“…Previous work has suggested that Cdk2 phosphorylation of Mcm2 stimulates phosphorylation by Cdc7 (9). Importantly, Cdc7-dependent phosphorylation was primarily measured as an increased amount of Mcm2 with altered mobility in SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kit utilized an anti-phospho-Cdc7-Threonine376 monoclonal antibody to detect the CDK1/cyclin B phosphorylation of its specific substrate, Cdc7. Hence, detection of a phosphorylated form of Cdc7 was proportional to the relative amount of activated cyclin B1-CDK1 kinase in the transfected and control cells (Masai et al, 2000). Our results demonstrated that HEK293 cells transfected with the vector alone showed moderate cyclin B1-CDK1 kinase activities.…”
Section: Tspy Interacts and Modulates Cyclin B-cdk1 Activities Y LI Amentioning
confidence: 49%
“…Kinase Assay-Purified Cdc7-ASK kinase complex (22) was mixed with 2 g of recombinant protein (Tob, proliferating cell nuclear antigen, or MCM2) in kinase buffer (40 mM HepesNaOH, pH 7.4, 10 mM MgCl 2 , 1 mM ␤-glycerophosphate, 1 mM sodium fluoride, 2 mM DTT, 200 M ATP), and reactions were carried out at 30°C for 30 min after the addition of [␥-…”
Section: Methodsmentioning
confidence: 99%